Analisis Kinerja Pemungutan Pajak Dan Restibusi Daerah Di Kabupaten Kabupaten Lombok Tengah - Zikriani, Santun Wahyu; Nurabiah (Fakultas Ekonomi dan Bisnis Unram, 2025)
The purpose of this study is to analyze the level of success of regional tax and regional levy collection in the Central Lombok Regency Government. The type of research used in this study is the descriptive analysis method with a quantitative approach. This study took place or location at the Central Lombok Regency Financial and Asset Management Agency. The data obtained by the researcher is quantitative. Quantitative because it is a Report on Targets and Realization of Taxes and Levies for the Central Lombok Regency Government for 3 years with the period 2021-2023. The results of this study include the effectiveness or level of success of regional tax collection in Central Lombok Regency in general or overall for the last 3 years, namely 2021 - 2023, it can be concluded that its effectiveness is included in the ineffective criteria with an average level of tax success of 74.225. The effectiveness or level of success of regional levy collection in Central Lombok Regency in general or overall for the last 3 years, namely 2021-2023, it can be concluded that the average success of the levy is 59.41%.